An Ophthalmology Resident-Led Quality Improvement Initiative to Decrease the Incidence of Perioperative Corneal Injury - Ely, Amanda L.; Goerlitz-Jessen, Mark; Scott, Ingrid U.; Lehman, Erik; Ali, Tabassum; Kerchner, Denise; Liang, David (Journal of Academic Ophthalmology, 2019)
Objective This article evaluates the effectiveness of an ophthalmology resident-led quality improvement (QI) initiative to decrease the incidence of perioperative corneal injury at an academic medical centerDesign Retrospective chart review.Methods A retrospective chart review was conducted of all surgical cases performed 6 months prior to, and 6 months after, implementation of an ophthalmology resident-led QI initiative at an academic medical center. The QI initiative (which focused on perioperative corneal injury awareness, understanding of risk factors, and presentation of an algorithm designed to prevent perioperative corneal injury) consisted of a lecture and distribution of educational materials to anesthesia providers. Data collected through the chart review included type of surgical case, presence of diabetes mellitus or thyroid disease, patient age and gender, patient positioning (supine, prone, or lateral), level of anesthesia provider training, length of surgical case, surgical service, type of anesthesia, and type (if any) of perioperative eye injury. The rates of perioperative corneal injury pre- versus post-initiative were compared.Results The rates of perioperative corneal injury pre- and post-initiative were 3.7 and 1.9 per 1,000, respectively (p = 0.012). Significant risk factors for perioperative corneal injury include longer duration of surgery (odds ratio [OR] 90–180 vs. < 90 minutes = 4.18, 95% confidence interval [CI] 1.43–12.18; OR > 180 vs. < 90 minutes = 8.56, 95% CI 3.01–24.32; OR > 180 vs. 90–180 = 2.05, 95% CI 1.17–3.58), patient position lateral > prone > supine (OR prone vs. lateral = 0.25, 95% CI 0.09–0.67; OR supine vs. lateral = 0.13, 95% CI 0.07–0.23), nonhead and neck surgeries (OR = 0.32, 95% CI 0.11–0.87), and surgery performed under the general surgery service (OR general surgery service vs. other subspecialty services = 6.50, 95% CI 2.39–24.76).Conclusions An ophthalmology resident-led QI initiative consisting of educating anesthesia providers was associated with a significant decrease in the rate of perioperative corneal injury.
Keywords: perioperative corneal injury; corneal abrasion; exposure keratopathy; quality improvement initiative